Junctional epidermolysis bullosa without pyloric atresia due to ITGB4 mutation. A new familial case diagnosed with prenatal genetic analysis and review of 13 literature cases. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2023)
Junctional epidermolysis bullosa (EB) linked to ITGB4 mutations may present, in addition to cutaneous signs, gastrointestinal (pyloric atresia) and urinary tract disorders, because the transmembrane protein ITGB4 is widely represented in the skin, gastrointestinal and urinary tract. In the present report we presented a case of junctional EB without pyloric atresia and without urinary signs at the time of observation. Genetic diagnosis was made during fetal life on amniotic fluid due to the presence of an older brother affected by the same disease. Furthermore, the review of the 13 literature cases of junctional EB without pyloric atresia linked to ITGB4 mutations highlighted the presence of severe urinary signs in 6 cases.